The Effectiveness of Islamic-Based Group Counseling Services on Students’ Character Development and Psychological Well-Being: A Literature Review - Meita, Yusra; Darimis, Darimis (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This literature review examines the effectiveness of Islamic-based group counseling services in fostering students’ character development and psychological well-being. The purpose of this study is to synthesize empirical findings from the last decade (2015–2025) regarding how Islamic values integrated into group counseling influence students’ character formation and mental wellness. Data were collected through systematic searches of academic databases and analyzed using a thematic narrative approach. The results show that Islamic-based group counseling significantly enhances students’ self-discipline, responsibility, religiosity, self-efficacy, and self-regulation. Additionally, it promotes greater emotional stability and interpersonal harmony. Despite these promising findings, several studies reported limitations such as small sample sizes, short intervention durations, and limited longitudinal assessments. The novelty of this review lies in its dual focus on both character and psychological well-being under an Islamic counseling paradigm, offering implications for future school counseling practices and research.